2018
DOI: 10.2196/11281
|View full text |Cite
|
Sign up to set email alerts
|

Features, Behavioral Change Techniques, and Quality of the Most Popular Mobile Apps to Measure Physical Activity: Systematic Search in App Stores

Abstract: BackgroundIt is estimated that 23% of adults and 55% of older adults do not meet the recommended levels of physical activity. Thus, improving the levels of physical activity is of paramount importance, but it requires the use of low-cost resources that facilitate universal access without depleting the health system. The high number of apps available constitutes an opportunity, but it also makes it quite difficult for the layperson to select the most appropriate app. Furthermore, the information available in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 20 publications
6
31
2
2
Order By: Relevance
“…All apps included some BCTs that may promote adherence to PA, and the higher-quality apps included a greater number of BCTs. No app contained more than 7 BCTs, which is similar to the findings of reviews of apps targeting PA in the general population [ 41 , 43 , 46 , 47 ]. Although the optimum number of BCTs needed to support PA adherence is not known, a recent systematic review including 8 randomized controlled trials (1018 participants) found that interventions with less than 7 BCTs were most effective at enhancing adherence to exercise in people with persistent musculoskeletal pain [ 48 ].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…All apps included some BCTs that may promote adherence to PA, and the higher-quality apps included a greater number of BCTs. No app contained more than 7 BCTs, which is similar to the findings of reviews of apps targeting PA in the general population [ 41 , 43 , 46 , 47 ]. Although the optimum number of BCTs needed to support PA adherence is not known, a recent systematic review including 8 randomized controlled trials (1018 participants) found that interventions with less than 7 BCTs were most effective at enhancing adherence to exercise in people with persistent musculoskeletal pain [ 48 ].…”
Section: Discussionsupporting
confidence: 69%
“…This finding is consistent with reviews of publicly available rheumatology self-management apps [ 20 - 22 ] and apps targeting PA and exercise in the general population [ 41 , 42 ]. For example, Simoes et al [ 43 ] identified 51 moderate-quality PA apps for use by the general population (MARS total score 3.16 to 4.41) with the functionality and esthetics domains scoring most highly. This is broadly similar to our findings and suggests that the included apps were intuitive, logical to follow, easy to learn and navigate, which is particularly important for people with RA who may have fatigue or hand and wrist disability [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study [134], the authors only described the features of this mobile application. In a study [135], it was reported to use for data acquisition.…”
Section: Carb Manager -Keto and Low Carb Diet Trackermentioning
confidence: 99%
“…The PAUL project aims to understand how the physical activity of city dwellers can be increased using custom apps [15]. It is observed that different apps to stimulate people to exercise exercise use different strategies [6]. The way to encourage more exercise, or at least maintain the same level of activity, varies and can be motivational messages, games, or peer comparison.…”
Section: Amsterdam Smart City Platformmentioning
confidence: 99%
“…This helps to personalize strategies and interventions aiming to increase physical activity and decrease sedentary behavior as well as goal setting [5]. Most mobile applications (apps) related to health, well-being, and physical exercise are not properly validated or under the supervision of health professionals, even though some are quite popular and well rated by users [6]. Privacy concerns also arise when apps collect and store data.…”
Section: Introductionmentioning
confidence: 99%